Mechanical characterization of dual phase austempered ductile iron - Basso, Alejandro Daniel (2010)
The fatigue behavior and mechanical properties of Dual Phase Austempered Ductile Iron (Dual Phase ADI) containing 20, 50, and 70% ausferrite were studied and compared to ductile irons with fully ferritic and ADI matrices. The results indicate that as the amount of ausferrite increases, tensile strength, yield stress, fracture toughness and fatigue resistance increase significantly, if compared to fully ferritc ductile irons. The elongation diminishes; nevertheless all Dual Phase ADI matrices have a deformation until failure that satis-fies the minimum value required by ASTM A 536 standard for ferritic ductile iron. All tensile properties of the samples containing 20% ausferrite, located in the last to freeze zones, increased; and so did the endurance limit about 25%. The fact that Dual Phase ADI could offer a wide range of mechanical properties, as a function of the relative percentage of free ferrite and ausferrite, led to the assumption that it could be used in safety parts, thereby replacing ductile irons with other matrices.